Consumer optimization of winter squash (cucurbita maxima duchesne) ice cream using mixture responce surface methodology - Magdaraog,Liezel G.
An acceptable winter squash ice cream was developed using consumer optimization and standardization following the mixture response surface methodology (RSM). The component avriables set for the optimization procedure were evaporated milk, squash and white refined sugar which comprised 46% of the total ice cream formula. Consumer response variables were acceptance of aroma, color mouthfeel, sweetness, flavor and overall acceptance of the ice cream. Fifty untrained panelists were randomly chosen as respondents for the sensory evaluation of the ice cream samples. Samples were rated for their response variables using the 9-point hedonic scale. Mean scores of consumer ratings were used to generate contour plots for each attribute. A determined optimum formulation of winter squash ice cream from the overlapped contour plots of significant (R2 > 0.70) attributes was verified and standardized. Results of RSM showed that formulations of squash ice cream containing 0 to 26.0% milk, 21 to 38.0% squash, and 42 to 85% sugar produced acceptable winter squash ice cream. Verification of the predictive model equations revealed that the models were valid and reproducible. Standardization of the optimum formulation containing 14% milk, 33% squash and 53% sugar of the total weight constituted by the three ingredients suggested it is repeatable.